The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.organomet.2c00013
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Imido NHC Complexes for Ring-Closing Olefin Metathesis Reactions

Abstract: Vanadium bis-phosphine imido and oxo chloride alkylidenes have been extensively applied in the ring-closing metathesis of various acyclic olefins. However, their reactions involving ethylene have shown limited productivity due to rapid decomposition. The primary degradation pathway involving V bis-phosphine imido complexes is β-H elimination at an unsubstituted metallacyclobutane. In contrast, β-H elimination is disfavored for V oxo species, but bimolecular decomposition precludes its high productivity. Herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…More recently, in a different [V]-carbene class, one of the ketamides was replaced by an aryloxy ligand V V (CHSiMe 3 )­(NAr)­(O-2,6- i Pr 2 C 6 H 3 )­(PMe 3 ) (Scheme c), showing the highest catalytic activity so far toward the ROMP of norbornene and other strained olefins. , This latter case triggered a family of complexes with enhanced catalytic activity, including a type of complex with a fluorinated alkoxy ligand V V (CHSiMe 3 )­(NR)­[OC­(CF 3 ) 3 ]­(PMe 3 ) 2 (Scheme d) that catalyzes cis -specific ROMP and is thermally robust. , Lately, vanadium carbenes with both imido (Scheme e) and oxo (Scheme f) ligands have been used to catalyze ring-closing metathesis, and their computational studies have shown that β-hydride elimination plays a subordinate role in deactivating the reaction. Both Schrock carbene catalysts and this family of [V]-carbene above described are high-oxidation early transition metal complexes with similarities, such as bearing ketamide and an alkoxide ligand, as well as the metal center in its highest oxidation center.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in a different [V]-carbene class, one of the ketamides was replaced by an aryloxy ligand V V (CHSiMe 3 )­(NAr)­(O-2,6- i Pr 2 C 6 H 3 )­(PMe 3 ) (Scheme c), showing the highest catalytic activity so far toward the ROMP of norbornene and other strained olefins. , This latter case triggered a family of complexes with enhanced catalytic activity, including a type of complex with a fluorinated alkoxy ligand V V (CHSiMe 3 )­(NR)­[OC­(CF 3 ) 3 ]­(PMe 3 ) 2 (Scheme d) that catalyzes cis -specific ROMP and is thermally robust. , Lately, vanadium carbenes with both imido (Scheme e) and oxo (Scheme f) ligands have been used to catalyze ring-closing metathesis, and their computational studies have shown that β-hydride elimination plays a subordinate role in deactivating the reaction. Both Schrock carbene catalysts and this family of [V]-carbene above described are high-oxidation early transition metal complexes with similarities, such as bearing ketamide and an alkoxide ligand, as well as the metal center in its highest oxidation center.…”
Section: Introductionmentioning
confidence: 99%
“…The main degradation pathway for catalysts 5 is the exchange of NHC to phosphine that forms during the initiation step, leading to a bis phosphine complex analogous to 3, which is unstable toward ethylene. 21 The next logical step for the catalyst optimization is the synthesis of V oxo NHC alkylidenes to preserve remarkable stability toward β-H elimination of V oxo complexes and disfavor bimolecular decomposition by introducing a large NHC ligand. In addition, we hypothesized that the shift to phosphine-free V oxo alkylidenes would improve catalyst performance, since phosphines can participate in side reactions and deactivation pathways, such as reduction of highoxidation-state V complexes 22 and reaction with alkylidenes.…”
mentioning
confidence: 99%
“…Recently, our group has developed V catalysts for ring-closing metathesis (RCM) of internal and terminal olefins and reported the highest V-based OM productivity involving terminal dienes. Representative V alkylidene complexes 3 – 5 and their productivities (turnover numbers, TONs) in RCM involving the model substrate 1 are shown in Scheme . The dissociation of one neutral ligand is required to access four-coordinate 14-electron active catalysts 3a – 5a during the reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR monitoring of the reaction of 4 with B(C6F5)3 by revealed that the sole reaction prod-uct observed was Me3SiHC=CHSiMe3 (cis/trans mixture), additionally identified by GC-MS spectrometry. These results clearly suggest a decomposition pathway via dimeric alkylidene coupling 25),26),29), 30) . In addition, these results also contrast with the formation of another alkylidene species after addition of B(C6F5)3 into a…”
Section: Discussionmentioning
confidence: 66%